2015
DOI: 10.1007/s11060-015-1912-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as potential biomarkers in Glioblastoma

Abstract: Glioblastoma is the most aggressive and lethal tumour of the central nervous system and as such the identification of reliable prognostic and predictive biomarkers for patient survival and tumour recurrence is paramount. MicroRNA detection has rapidly emerged as potential biomarkers, in patients with glioblastoma. Over the last decade, analysis of miRNA in laboratory based studies have yielded several candidates as potential biomarkers however, the accepted use of these candidates in the clinic is yet to be va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 112 publications
2
37
0
Order By: Relevance
“…However, due to inconsistencies in the reported subset of miRNAs that are either up or down-regulated in GBM IV, a specific miRNA signature is not yet well established. Notably, miR-21 is the only miRNA found to be up-regulated in tumor tissues from GBM IV across all the studies, whereas among the down-regulated miRNAs, miR-132 is the most consistent, although it was identified only in 60% of the reported analyses (10). The quality of tumor tissues, sample sizes, appropriateness of "control" brain tissue and analytical techniques could explain discrepant results obtained across the published studies.…”
Section: Mirna Expression Profiles In Gliomasmentioning
confidence: 90%
See 1 more Smart Citation
“…However, due to inconsistencies in the reported subset of miRNAs that are either up or down-regulated in GBM IV, a specific miRNA signature is not yet well established. Notably, miR-21 is the only miRNA found to be up-regulated in tumor tissues from GBM IV across all the studies, whereas among the down-regulated miRNAs, miR-132 is the most consistent, although it was identified only in 60% of the reported analyses (10). The quality of tumor tissues, sample sizes, appropriateness of "control" brain tissue and analytical techniques could explain discrepant results obtained across the published studies.…”
Section: Mirna Expression Profiles In Gliomasmentioning
confidence: 90%
“…Large-scale miRNA expression analyses reported both the up-regulation and down-regulation of several miRNAs in tumour tissues from patients with GBM IV compared to normal brain tissue, which could hence permit a more reliable and consistent diagnosis (10). However, due to inconsistencies in the reported subset of miRNAs that are either up or down-regulated in GBM IV, a specific miRNA signature is not yet well established.…”
Section: Mirna Expression Profiles In Gliomasmentioning
confidence: 99%
“…Most miRNAs simultaneously regulate multiple targets, thereby conducting multifaceted changes in protein expression [5,49,50]. Several miRNAs have been identified that correlate to clinical outcomes and modulate glioblastoma proliferation and invasion [9,[50][51][52]. In an effort to elucidate the signaling mechanisms that regulate the switch from proliferation to invasion in malignant glioma, we performed LCMD to isolate glioma cells from the primary tumor and from invasive tumor islets located >100 μm from the tumor boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant gene expression is the primary mechanism of miRNA dysfunction in cancer, and miRNAs are differentially expressed in gliomas relative to normal tissue [7,8]. Consequently, miRNAs have rapidly emerged as potential biomarkers in patients with glioma [9,10]. Multiple miRNAs have now been linked to glioma malignancy, and several have been identified to regulate tumor cell motility and division [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation